Pola Penggunaan Lahan Berdasarkan Kelas Kemampuan Lahan di Sub-sub DAS Kunisi Hulu DAS Jeneberang Kabupaten Gowa - Wahyuni wahyuni; Usman Arsyad; Anwar Umar; Reza Ashari Wirawan (Jurnal Hutan dan Masyarakat, 2018)
The research aims to determine the extent of land use suitability with land capability in Kunisi subs watershed of Jeneberang’s upstream watershed. This research is expected to provide guidelines and consideration for related institution in conducting socialitation and enlightment in the field of soil conservation for farmers at Manimbahoi and Bilanrengi Village of Gowa regency. The method used in this study was image analysis by using software GIS and field observations conducted in Kunisi subs watershed of Jeneberang’s upstream watershed. The research was carried from December 2014 to January 2015. The results showed that the uses of land in the subs watershed of Kunisi were for forest, gardens, rice fields, and shrubs with various level of land capability qualification IIIE, IIIb, IIIk, IVe, IVl, Vp, VIl, and VIIl. In the land unit found in the field there was mismatch land capability and land use. Such discrepancy can be resolved by restoring the function of land use based on its relevance and implement appropriate soil conservation techniques based on land capability classes